Patogênese e terapia experimental da infecção pelo alfaherpesvírus bovino 2 - Amaral, Bruna Portolan (2020)
Bovine alphaherpesvirus 2 (BoHV-2) - the agent of bovine herpetic mamillitis (BHM) – is related to Human alphaherpesviruses 1 and 2 (HHV-1, HHV-2) and has been proposed as a model for vaccine and drug testing. In addition, very little is known about the pathogenesis of BoHV-2 infection. Herein we studied the pathogenesis of BoHV-2 in calves after inoculation through different routes and investigated the activity of candidate anti-viral drugs in vitro and in vivo against BoHV-2. In the first study, 3 to 4-months-old calves were inoculated with BoHV-2 (107TCID50.mL-1) intramuscularly (IM, n=4), intravenously (IV, n=4) or transdermally (TD) after mild scarification (n=4) and monitored thereafter. Calves inoculated by the IV route presented as light increase in body temperature between days 6 to 9 post-inoculation (pi). Virus inoculation by the TD route resulted in mild inflammatory lesions at the sites of inoculation, characterized by hyperemia, small vesicles, mild exudation and scab formation, between days 2 and 8pi.Virus or viral DNA was detected by PCR in the crusts/swabs collected from lesions of 3 out of 4 animals inoculated TD from day 2 to 8pi. Viremia was detected in 3/4 animals of the IM group (from day 4 to 8pi); in 2/4 animals of the IV group (days 6 and 8pi) but not in the TD group. Administration of dexamethasone (Dex) to the inoculated calves at day 48pi, did not result in virus reactivation. In the second study, we investigated the anti-viral activity in vitro against BoHV-2 of three anti-herpetic drugs: Cidofovir (CDV), Fanciclovir (FAM), Foscarnet (PFA), and diphenyl disselenide (PhSe)2 by plaque reduction assays (PRA). A significant reduction in the number of viral plaques was observed by treating the monolayers with (PhSe)2 (79.7% reduction, p<0.05) or CDV (62.8%, p<0.05). FAM treatment resulted in a slight decrease in plaque number (22.9%, p<0.05) and PFA showed no anti-viral activity. Next, we investigated the effects of (PhSe)2 and CDV, alone or in combination, in the infection and disease produced by BoHV-2 in ewes inoculated transdermally and submitted to topic treatment with a vehicle gel containing (PhSe)2, CDV, and combined (PhSe)2 + CDV. Thirteen out of 14 (92.8%) inoculated ewes developed local lesions that typically progressed through the stages of hyperemia (days 2 – 6pi), large papules or depressed/flat dark areas (day 4 to 12pi), accompanied/followed by scab/crust formation that lasted beyond day 15pi in untreated ewes. Treatment with (PhSe)2 resulted in an important reduction in clinical score from day 8 pi onwards (p<0.05), shortening of clinical course and reduction in duration of virus shedding (p<0.05) compared to untreated controls. Combined ((PhSe)2+CDV) treatment and CDV alone, also led to clinical improvement (p<0.05), yet less pronounced and delayed (after day 11 pi and 13 pi, respectively), but no significant reduction in virus shedding. Taken together, these findings contribute to the knowledge of BoHV-2 pathogenesis and are promising towards the use of diphenyl disselenide (PhSe)2, alone or in combination with anti-herpetic drugs, in the treatment of lesions induced by BoHV-2 in the udder and teats of dairy cows.